Pemeriksaan Bercak Darah pada Kain yang Direndam & Dikubur Menggunakan Tes Teichmann - Puji Anugrah; Citra Manela; Syamel Muhammad (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Blood is the most important physical evidences and often found at crime scene. The Teichmann test is a confirmation test to check whether the spot really a blood.Objective. This study aims to identify the bloodstain on cloth soaked in water and buried in the ground using Teichmann test.Method. The research type is a descriptive study with a laboratory experimental study design. The sample of this study was a cloth dripped with blood, 27 samples are immersed in a bucket filled with water and 27 other samples are buried in the ground with a depth of 20 cm. The examination using the Teichmann test will be carried out on the 6th to the 14th day of exposure.Result. From the research that has been done, the results of the Teichmann test were positive on blood spots on cloth soaked in water and buried in the ground on the 6th to 9th day of exposure. Positive results indicate the formation of hemin hydrochloride crystals in the form of blackish-brown rods.Conclusion. The conclusion of this study is hemin hydrochloride crystals can still be found in blood stains on cloth soaked in water and buried in the soil using the Teichmann test but limited to the 9th day of exposure.